Examination of the Cell Cycle Dependence of Cytosine and Adenine Base Editors - Burnett, Cameron A.; Wong, Ashley T.; Vasquez, Carlos A.; McHugh, Colleen A.; Yeo, Gene W.; Komor, Alexis C. (Frontiers in Genome Editing, 2022)
Base editors (BEs) are genome editing agents that install point mutations with high efficiency and specificity. Due to their reliance on uracil and inosine DNA damage intermediates (rather than double-strand DNA breaks, or DSBs), it has been hypothesized that BEs rely on more ubiquitous DNA repair pathways than DSB-reliant genome editing methods, which require processes that are only active during certain phases of the cell cycle. We report here the first systematic study of the cell cycle-dependence of base editing using cell synchronization experiments. We find that nickase-derived BEs (which introduce DNA backbone nicks opposite the uracil or inosine base) function independently of the cell cycle, while non-nicking BEs are highly dependent on S-phase (DNA synthesis phase). We found that synchronization in G1 (growth phase) during the process of cytosine base editing causes significant increases in C•G to A•T “byproduct” introduction rates, which can be leveraged to discover new strategies for precise C•G to A•T base editing. We observe that endogenous expression levels of DNA damage repair pathways are sufficient to process base editing intermediates into desired editing outcomes, and the process of base editing does not significantly perturb transcription levels. Overall, our study provides mechanistic data demonstrating the robustness of nickase-derived BEs for performing genome editing across the cell cycle.